Assessing how changes in land use affect runoff and water quality in Palembang, South Sumatra, Indonesia - Yusuf, Maulana; Damiri, Nurhayati; Saptawan, Ardiyan; Yunardy, Syafrul (Brawijaya University, 2024)
The concerns about the conversion of swamp land into settlements and its effect on the quality of river water are urgent in Indonesia as a developing country. This research evaluated how changes in land use in the Keramasan region of Palembang, South Sumatra, affect the water quality of the Pedado River. Physical, chemical, and microbiological characteristics of the water were gathered in 2017 and 2022 from four monitoring points along the Pedado River. Pollution indicators were used to evaluate the state of river water quality. The results showed that land conversion operations increased flow from the mainland into the Pedado River and the loss of swamp vegetation. One such activity in 2022 was the backfilling of 42.92 hectares of swampland. Total suspended solids (TSS), copper (Cu), oil, and fat in the Pedado River surpassed the quality limits of class II, according to Government Regulation of the Republic of Indonesia Number 82 of 2001, based on measurements of the water quality in the Keramasan region. The Pedado River's water pollution status changed from mildly contaminated in 2017 (pollution index: 3.728-4.940) to moderately polluted in 2022 (pollution index: 5.395-6.236). These results highlight the critical need for thorough water treatment and preventative actions to lessen further contamination in the Pedado River.